A Comparative Assessment of Thermodynamic and Exergoeconomic Performances of Three Thermochemical Water-Splitting Cycles of Chlorine Family for Hydrogen Production. (1st November 2022) - Razi, Faran; Hewage, Kasun; Sadiq, Rehan
Highlights: Thermodynamic and exergoeconomic analyses of three thermochemical cycles of chlorine family. Thermal management schemes incorporated for each cycle considering both industrial waste heat and internal heat recovery. Application of the specific exergy costing (SPECO) and energy and exergy approaches. Hydrogen production capacity of 0.185 kg/s for each thermochemical cycle. Abstract: Hydrogen production processes utilizing hydrocarbon-based sources as feedstocks have severe environmental implications (when not incorporating carbon capturing and storage technology) in addition to resulting in depletion of non-sustainable naturally occurring fuel sources. In this regard, thermochemical water-splitting is an extremely environmentally benign pathway for obtaining sustainable hydrogen. Thus, this paper studies and comparatively evaluates three different thermochemical cycles of the chlorine family for hydrogen production which include iron-chlorine, copper-chlorine, and magnesium-chlorine cycles. Each cycle is first modeled and simulated in Aspen-plus and then analyzed from thermodynamic and exergoeconomic viewpoints. A thermodynamic and exergoeconomic performance comparison of the three thermochemical cycles is further performed in terms of their overall efficiencies, net heat input and rejection rates, exergy destruction rates, unit costs of hydrogen, hourly levelized cost rates, and cost rates of exergy destruction. All cycles are modeled and simulated by considering the incorporation of waste heat recovery from a steel plant and internal heat recovery within each cycle to improve the process efficiencies by reducing the overall thermal energy consumption. According to the performed analyses, the copper-chlorine cycle has the highest energy (79.7%) and exergy (81.1%) efficiencies followed by the iron-chlorine cycle (energy and exergy efficiencies of 48.8% and 49.6%, respectively) with the magnesium-chlorine cycle exhibiting the lowest overall energy (19.8%) and exergy (20.2%) efficiencies. Moreover, the iron-chlorine cycle demonstrates the lowest unit cost of hydrogen (0.7 $/kg) followed by the copper-chlorine cycle (4 $/kg) with the magnesium-chlorine cycle exhibiting an extremely high unit hydrogen cost (8.9 $/kg). This study also identifies certain key factors that largely impact the cost of hydrogen and comprehensively discusses the influence and extent of each factor on the cost of hydrogen.